Educación sanitaria en la sostenibilidad del servicio de saneamiento, caserío Tayo Grande - Cascas – 2022 - Zarate Asto, Denix Erict (2022)
The objective of this work is to explain how health education that includes hygiene habits at home and the socioeconomic assessment of the sanitation service influences the sustainability of sanitation services in the Caserío Tayo Grande - Cascas. For the investigation, we worked mainly with a sample composed of the universe of 22 active associates of the Sanitation Service Users Board and additionally, the JASS Board of Directors participated, as well as the prosecutor and the SAP operator. Based on ethnographic-ethnological and statistical methods, research techniques were carried out, including focus groups, surveys, direct observation and documentary review, in which instruments such as guides for focus groups, questionnaires, cameras, voice recorders and notebooks were used. field. In this framework, a significant gap was identified in households that have not yet adopted adequate practices of body hygiene, in food and in the home environments, in the same way the socioeconomic assessment of sanitation services by users has not yet been adopted. It is optimal because delinquency of the family quota, inappropriate use of water resources and damage to the SAP infrastructure and unattended home connections have been identified. All this, added to the weaknesses in the management of the Board of Directors, is causing certain deficiencies in the SAP that translate into the affectation of the quality and quantity of water; as well as in the continuity of the service.